A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Première publication 1892 https://docsouth.unc.edu/church/cooper/cooper.html
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Se défendre : une philosophie de la violence - Dorlin, Elsa (Zones, 2017)
"En 1685, le Code noir défendait " aux esclaves de porter aucunes armes offensives ni de gros bâtons " sous peine de fouet. Au xixe siècle, en Algérie, l'État colonial français interdisait les armes aux indigènes, tout en accordant aux colons le droit de s'armer. Aujourd'hui, certaines vies comptent si peu que l'on peut tirer dans le dos d'un adolescent tout en prétendant qu'il était agressif, armé et menaçant. Une ligne de partage oppose historiquement les corps " dignes d'être défendus " et ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce " désarmement " organisé des subalternes et des opprimés au profit d'une minorité jouissant d'un droit permanent à porter des armes et à en user impunément pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Du jiu-jitsu des suffragettes aux pratiques insurrectionnelles du ghetto de Varsovie, des fusils des Black Panthers aux patrouilles queer, Elsa Dorlin retrace une généalogie philosophique de l'autodéfense politique. Derrière l'histoire officielle de la légitime défense, il est ici question du récit des " éthiques martiales de soi ", ces histoires ensevelies où le Sujet ne préexiste pas à sa propre défense, où le fait de se défendre en attaquant apparaît à la fois comme la condition de possibilité d'un soi et la matière des mythologies politiques. Cette histoire - une histoire de la violence - conditionne la définition même de la subjectivité moderne. Elle s'écrit à la lumière d'une relecture critique de l'histoire de la philosophie politique, où Hobbes et Locke sont à confronter avec Franz Fanon, Michel Foucault ou Judith Butler."–Page 1 et 4 de la couverture.
Keywords: afro-féminisme; approches et analyses; cours; discipline; fem3100; féminisme afroaméricain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; philosophie; premier cycle; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

THE COLOURED WOMEN’S CLUB OF MONTREAL, 1902-1940: African-Canadian women confronting anti-black racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review, 2017)
À ce jour, il existe très peu d’écrits sur la contribution des personnes d’ascendance africaine à l’histoire de l’assistance sociale canadienne. À partir de sources secondaires et archivistiques, nous analysons la contribution du Club des femmes de couleur de Montréal (CFCM) au bien-être de la communauté noire de Montréal entre 1902 et 1940 du point de vue du racisme contre les Noir.e.s et du féminisme afro-canadien. Le CFCM a joué un rôle prépondérant dans ce bien-être en étant l’un des grands soutiens auprès des membres aux prises avec d’importantes difficultés dans une société où le racisme était omniprésent et où les perspectives d’avenir pour les hommes et les femmes étaient fortement limitées. Le club a organisé plusieurs activités qui ont permis aux membres de la communauté de survivre dans un milieu hostile aux personnes d’ascendance africaine. Il a ainsi été d’un grand secours et a favorisé un sentiment de communauté chez les Noir.e.s de Montréal. Nous avançons que, grâce aux efforts de ce club durant cette période, les Afro-Canadiennes sont d’abord devenues des actrices clés de la communauté et ensuite les premières intervenantes sociales. Il est impératif que les travailleurs sociaux reconnaissent la contribution des femmes engagées dans le CFCM afin de faire contrepoids aux récits historiques de notre profession qui proviennent surtout d’une culture hégémonique blanche.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; fem3100; femmes* afro-descendantes; histoire et politique; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Femmes autochtones: la violence coloniale et ses avatars - Perreault, Julie (Relations, 2017)
Au Québec et au Canada, les femmes autochtones sont parmi les plus susceptibles d'être la cible de violences; une réalité qui met en lumière une histoire de colonialisme qui continue de faire des victimes.
Keywords: amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; québec; racisme; régions géographiques; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Expertes en genre et connaissances féministes sur le développement. Qui sait ? - Verschuur, Christine (Graduate Institute Publications, L'Harmattan., 2017)
Depuis la quatrième Conférence mondiale sur les femmes à Beijing, on observe une forte augmentation du nombre de personnes expertes en genre. Celles-ci circulent, tout comme les pratiques, les idées, les théories et les textes féministes qui voyagent sont interprétés, resignifiés. Des inégalités existent dans les processus d’élaboration, la circulation et la traduction des savoirs. Le champ social constitué par les expertes en genre est ainsi traversé par des rapports de pouvoir. La notion de colonialité du pouvoir et des savoirs permet d’interroger l’hégémonie et l’autorité universelle des discours et des savoirs occidentaux. Les contributions des études féministes pour revisiter le développement sont soulignées dans cet ouvrage. Ces apports, énoncés depuis diverses perspectives, s’inscrivent dans des espaces de contestation de l’ordre mondial, sont nourris de la prise de conscience des multiples rapports de domination et de l’émergence de nouveaux mouvements sociaux. Ils participent d’un processus de décolonisation de la pensée féministe. Avec la collection « Genre et développement. Rencontres », nous poursuivons le dialogue de savoirs sur les questions féministes et de genre, la construction d’alliances et de ponts entre chercheur-es, organisations féministes et de recherche, ONG, organisations de coopération, expertes, aux Nords et aux Suds. Les textes, écrits par des chercheur-es ou personnes actives dans ces initiatives sont publiés dans leur langue originale.
Keywords: anthropologie; approches et analyses; discipline; féminisme décolonial; féminisme matérialiste; histoire et politique; patriarcat; projet charge mentale; pédagogie; racisme; ressource en ligne; science politique; science politique et droit; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques